First Case Report of a Collodion Baby from Azad Jammu and Kashmir, Pakistan - Khushal, Saiqa; Shoukat, Rabiah; Hameed, Khalid; Khan, Muzammil Ahmed; Nisar, Rameez; Abbasi, Ansar Ahmed (BioScientific Review, 2023)
Collodion baby is a rare genetically determined congenital condition that follows an autosomal recessive pattern of inheritance resulting in a parchment-like tight, shiny skin present over the skin of the newborn. Due to this condition, the body surface of the newborn remains invisible. The current study was aimed to enlighten the case of a collodion baby in District Mirpur, Azad Jammu and Kashmir. In this case, the baby was born with a membrane-like sheet covering the whole body. Resultantly, the baby experienced tachypnea along with the deformation of the body, as well as ectropion and eclabium. Moreover, there was restricted or almost no movement of limbs. Initial treatment included continuous oxygen inhalation, skin care by using moisture agents, and a nasogastric tube implanted for feeding.